Entropy-driven reversible melting and recrystallization of layered hybrid perovskites - Rajput, Parikshit Kumar; Salunkhe, Parashurama; Sarma, Manmayuri; Basu, Meghasree; Gopal, Animesh; Joshi, Aprajita; Shingote, Ajinkya Sundarnath; Saha, Surajit; Rahman, Atikur; Nag, Angshuman (SMALL, 2024)
Keywords: hybrid perovskites; photodetector; reversible melting

Ultrabroad near infrared emitting perovskites - Saikia, Sajid; Gopal, Animesh; Rathod, Radha; Joshi, Aprajita; Priolkar, K. R.; Saha, Surajit; Santra, Pralay K.; Shanmuganathan, Kadhiravan; Nag, Angshuman (Angewandte Chemie-International Edition, 2025)
Phosphor converted light emitting diodes (pc-LEDs) have revolutionized solid-state white lighting by replacing energy-inefficient filament-based incandescent lamps. However, such a pc-LED emitting ultrabroad near-infrared (NIR) radiations still remains a challenge, primarily because of the lack of ultrabroad NIR emitting phosphors. To address this issue, we have prepared 2.5 % W4+-doped and 2.8 % Mo4+-doped Cs2Na0.95Ag0.05BiCl6 perovskites emitting ultrabroad NIR radiation with unprecedented spectral widths of 434 and 468 nm, respectively. Upon band-edge excitation, the soft lattice of the host exhibits broad self-trapped exciton (STE) emission covering NIR-I (700 nm), which then nonradiatively excites the dopants. The <img alt="mathematical equation" class="fallback__image" src="https://onlinelibrary.wiley.com/cms/asset/cbbb8722-f036-4e98-91f1-f78348f240a5/anie202415003-math-0001.png" style="box-sizing: border-box; border-style: none; max-width: 100%; vertical-align: middle; color: rgb(0, 0, 0); font-family: "Open Sans", icomoon, sans-serif; font-size: 16px;" /> –donor ligand Cl− reduces the energy of dopant d–d transitions emitting NIR-II with a peak at ~950 nm. Vibronic coupling broadens the dopant emission. The large spin-orbit coupling and local structural distortion might possibly enhance the dopant emission intensity, leading to an overall NIR photoluminescence quantum yield ~40 %. The composite of our ultrabroad NIR phosphors with biodegradable polymer polylactic acid could be processed into free-standing films and 3D printed structures. Large (170<img alt="mathematical equation" class="fallback__image" src="https://onlinelibrary.wiley.com/cms/asset/62119a49-ef5d-4b17-a727-798978412727/anie202415003-math-0002.png" style="box-sizing: border-box; border-style: none; max-width: 100%; vertical-align: middle; color: rgb(0, 0, 0); font-family: "Open Sans", icomoon, sans-serif; font-size: 16px;" /> 170 <img alt="mathematical equation" class="fallback__image" src="https://onlinelibrary.wiley.com/cms/asset/3d2c08c0-4ab8-436a-bc69-603df5328723/anie202415003-math-0003.png" style="box-sizing: border-box; border-style: none; max-width: 100%; vertical-align: middle; color: rgb(0, 0, 0); font-family: "Open Sans", icomoon, sans-serif; font-size: 16px;" /> ), robust, and thermally stable 3D printed pc-LED panels emit ultrabroad NIR radiation, demonstrating NIR imaging applications.